Multi-Product Exporters : Diversification and Micro-Level Dynamics - Iacovone, Leonardo; Javorcik, Beata S. (World Bank, Washington, DC, 2012)
Recent developments in trade theory, especially research on multi-product firms, have not been matched by similar progress on the empirical front. This paper aims to fill this gap by presenting a novel set of stylized facts on firm-product dynamics observed during an export boom. This exercise is possible thanks to a unique firm-product level dataset covering about 85 percent of Mexican industrial output for the period 1994-2003. The main findings are as follows. First, there is a substantial degree of product turnover at the firm-product level in response to declining trade costs. Second, "core competencies" - the fact that firms have a cost advantage or greater expertise at manufacturing some of their products - are the main driver of firms' decision to introduce or drop export products. Third, new exporters tend to "start small" in terms of both values and number of exported products. Fourth, even if the expansion in the number of exported products played a role in stimulating Mexican exports, the growth in volume of pre-existing products was the main driver of the export boom. Finally, the introduction of new export products is preceded by a surge in investment. These findings are in line with many, but not all, predictions of recent theoretical work.